Tubular composite material with internal thread and external fin structure and preparation process of tubular composite material

By performing internal thread processing in the titanium tube, applying a copper-aluminum alloy cladding layer to the outer layer, combined with diffusion and heat treatment, a tubular composite material with an internal threaded outer fin structure was prepared, which solved the problems of corrosion resistance and low heat exchange efficiency of the titanium tube heat exchanger, and achieved efficient and durable composite tube material.

CN119839582APending Publication Date: 2025-04-18CAS & GD METALLIC MATERIAL DEV CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510063099.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In chemical production, existing titanium tube heat exchangers have short service life and high maintenance costs due to their corrosion resistance and low heat exchange efficiency. Traditional corrosion-resistant materials such as copper and aluminum are not corrosion-resistant and are difficult to use separately.

Method used

Using a tubular composite material with an internal threaded outer fin structure, a composite tube with high bond strength is prepared by performing internal thread processing in the titanium tube and applying a copper-aluminum alloy cladding layer to the outer layer, combined with diffusion and heat treatment.

Benefits of technology

The temperature and pressure resistance of composite pipes are improved, the atmospheric corrosion resistance and heat exchange efficiency are enhanced, the production cost and energy consumption are reduced, and lightweight and diversified production is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839582A_ABST
    Figure CN119839582A_ABST
Patent Text Reader

Abstract

The invention relates to the field of composite material preparation, and discloses a tubular composite material with an internal thread and external fin structure and a preparation technology thereof.The preparation technology comprises the steps that a titanium pipe is selected, and internal thread machining is conducted in the titanium pipe; a copper-aluminum alloy is adopted as a surface cladding layer of a titanium tube, a small amount of titanium is added into the copper-aluminum alloy, stirring is conducted through an electromagnetic stirrer, and a refining agent is added in the stirring process for refining; the preparation method comprises the following steps: melting copper-aluminum alloy liquid, pretreating a titanium tube, inserting the titanium tube, emptying the titanium tube, discharging liquid, and carrying out cladding traction to prepare a composite alloy tube; in the preparation process of the composite alloy pipe, cladding traction is carried out, and then diffusion bonding heat treatment is adopted; the composite alloy pipe is machined to obtain an internal-thread external-fin tubular composite material; the problems that a composite pipe is low in temperature resistance and pressure resistance, prone to deformation, damage and leakage after resisting high-pressure washing, weak in atmospheric corrosion resistance, low in heat exchange efficiency, high in production cost and low in production efficiency are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite material preparation, and in particular to a tubular composite material with an internal thread and an external fin structure and a preparation process thereof. Background Art

[0002] As chemical production processes often involve various corrosive media, this can cause serious corrosion to the heat exchange tubes, thereby affecting the service life and heat exchange efficiency of the heat exchange tubes, increasing equipment maintenance costs, and may even lead to production interruptions. In order to solve the corrosion problem, chemical companies usually take a variety of measures. Among them, the use of corrosion-resistant materials to make heat exchange tubes is one of the common methods, such as using materials with good corrosion resistance such as titanium. However, the heat transfer coefficient of titanium is only the thermal conductivity of titanium λ = 15.24W / (m·K). Titanium is a new type of metal, and its thermal conductivity is about 1 / 4 of nickel, 1 / 5 of iron, and 1 / 14 of aluminum. The thermal conductivity of various titanium alloys is about 50% lower than that of titanium.

[0003] Therefore, the low efficiency of titanium tube heat exchangers has become an important factor restricting enterprise costs. If materials with higher heat transfer coefficients can be selected to replace traditional titanium tubes, their heat transfer efficiency can be greatly increased, thereby reducing energy consumption. However, traditional materials with relatively high heat transfer coefficients, such as copper and aluminum, are not suitable as heat exchange tubes for such working conditions due to their corrosion resistance. Therefore, it is necessary to produce a composite tubular composite material with high bonding strength to replace traditional titanium heat exchange tubes. The inner wall is made of titanium material for corrosion resistance, and the outer layer is an aluminum-copper composite material to increase heat transfer, achieve energy saving and consumption reduction, and reduce costs for enterprises. Summary of the invention

[0004] The present invention aims to provide a tubular composite material with an internally threaded external fin structure and a preparation process thereof, so as to solve the problems of low temperature and pressure resistance of the composite pipe, easy deformation, damage and leakage after high-pressure washing, weak resistance to atmospheric corrosion, low heat exchange efficiency, high production cost and low production efficiency.

[0005] In order to achieve the above object, the present invention provides the following method:

[0006] The present invention provides a tubular composite material with an internal thread and an external fin structure and a preparation process thereof:

[0007] S1: Select a titanium tube and perform internal thread processing in the titanium tube;

[0008] S2: using a copper-aluminum alloy as the surface cladding layer of the titanium tube, adding a small amount of titanium to the copper-aluminum alloy, stirring the alloy by an electromagnetic stirrer, and adding a refining agent during the stirring process for refining;

[0009] S3: melting the copper-aluminum alloy liquid, pre-treating the titanium tube, inserting the titanium tube, idling the titanium tube, draining the liquid, and performing cladding traction to prepare a composite alloy tube;

[0010] S4: During the preparation process of the composite alloy tube, cladding traction is performed, and diffusion bonding heat treatment is performed after the cladding traction step;

[0011] S5: Processing the outer fins of the composite alloy tube to obtain an internally threaded outer fin tubular composite material.

[0012] Preferably, the standards for the selected titanium tube are: the wall thickness of the titanium tube is 0.3mm-15mm, and the diameter is 5mm-80mm; the standards for the internal thread processing in the titanium tube are: the internal thread tooth height is 0.05mm-6mm; the tooth bottom wall thickness is 0.25mm-9mm; the tooth top angle is 25-75°; the number of internal threads is 35-500 / week; the tooth shape is special-shaped teeth or cross teeth.

[0013] Preferably, the contents of copper, aluminum and titanium in the surface cladding layer are as follows: copper content is 50%-70%, aluminum content is 30%-50%, and titanium content is 0.5%-1.5%.

[0014] Preferably, the stirring speed of the electromagnetic stirrer is 50-300 r / min, and the stirring time is 5-30 min; the refining agent is added during the stirring process for refining for 10-20 min.

[0015] Preferably, the step of pretreating the titanium tube by melting the copper-aluminum alloy liquid comprises: loading the copper-aluminum alloy into a melting furnace, heating it to a temperature of 1300°C using a heating coil and keeping it warm until all the aluminum is melted; simultaneously turning on the insulation furnace for heating, with the temperature set to be 10°C lower than the melting furnace temperature, to obtain an alloy melt; and cleaning and degreasing the titanium tube to remove dirt and oxide layer on the surface.

[0016] Preferably, the steps of inserting the titanium tube, running the titanium tube empty, and draining the liquid, performing cladding traction, and preparing the composite alloy tube include: the titanium tube inserting step is: opening the upper and lower traction rollers of the traction machine, inserting the titanium tube into the upper and lower traction rollers, until it passes through the upper traction roller, the center sleeve, the mold, and the lower traction roller, clamping the upper and lower traction rollers, inserting a protective gas delivery pipe into the upper end of the titanium tube, and continuously filling it with protective gas; the titanium tube running empty step is: opening the traction machine, using the traction roller to drive the titanium tube to run empty, and the speed is controlled at 20mm / min-100mm / min; the draining step is: opening the stopper rod, so that the alloy melt flows to the insulation furnace through the draining channel; the cladding traction step is: after the alloy melt enters the insulation furnace, the traction machine speed is adjusted to 100mm / min-1500mm / min, and cooling water is introduced for cooling, so that the alloy melt quickly crystallizes and is clad on the surface of the titanium tube to form a coating layer to obtain a composite alloy tube.

[0017] Preferably, in the preparation process of the composite alloy tube, cladding traction is performed, and after the cladding traction step, a diffusion combined heat treatment step is adopted, including: heating the composite alloy tube by raising the temperature of the heating furnace to 350°C-500°C, and maintaining the insulation state, the insulation pressure is 5MPa-15Mpa, and the insulation time is 2h-5h, so that the atoms can be fully diffused; after the insulation state ends, cooling the composite alloy tube by air cooling or water cooling.

[0018] Preferably, the step of processing the outer fin of the composite alloy tube to obtain an internally threaded external fin tubular composite material comprises: adjusting the rolling CNC blade through a fin rolling mill, performing on-machine rolling, rolling a circle of aluminum fins on the surface of the composite alloy tube to obtain an aluminum fin tube; trimming the two ends of the aluminum fin tube, removing the fins from the two ends of the aluminum fin tube, and obtaining an internally threaded external fin tubular composite material.

[0019] Preferably, the aluminum fins of the aluminum fin tube have a wall thickness of 0.5mm-15mm and a diameter of 5mm-80mm; the wall thickness of the composite alloy tube is 1mm-20mm and the diameter is 5.5mm-90mm; the spacing between the composite alloy tube and the mold is 0.5-10mm; the distance between adjacent aluminum fins is 1.8mm-10mm, the height is 0-20mm, and the thickness is 0.2-1mm.

[0020] Preferably, after the outer fins of the composite alloy tube are processed to obtain the internally threaded external fin tubular composite material, the method further includes: removing oil stains and oxidation layers on the surface of the internally threaded external fin tubular composite material through the steps of degreasing - removing oxidation film - cleaning - natural color passivation - cleaning and drying.

[0021] The beneficial effects of the present invention are embodied in that the composite pipe produced by the production process has high overall temperature and pressure resistance, will not be deformed, damaged or leaked after high-pressure washing, has strong atmospheric corrosion resistance and high heat exchange efficiency. The overall weight of the pipe is light and can achieve overall lightweight. At the same time, due to the overall use of the composite continuous casting production process, the overall production cost is low, the production efficiency is high, and long-size continuous production can be achieved. It can be produced over a long distance according to demand, without welding, without welds, and can effectively respond to special production needs. And through the directional combination of mold design and internal base pipe, composite pipes with different processes and different wall thicknesses are produced, thereby realizing diversified and customized production; wherein, the inner titanium tube has high strength and pressure bearing capacity, can maintain the overall rigidity of the element, is not prone to deflection and deformation, can be used for a long time, and plays a supporting structure role in the later overall structural combination of the heat exchanger, has strong pressure resistance, and can work stably in various harsh environments. In addition, the biggest advantage of the titanium tube is overall corrosion resistance, so it can flow through highly corrosive acid, alkali, and salt chemical solutions. The outer aluminum-copper cladding has excellent thermal conductivity, which can greatly improve the overall heat transfer efficiency of the component. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0023] Figure 1 It is a schematic diagram of a tooth shape structure of a special-shaped step tooth with an internal thread and an external fin structure provided by an embodiment of the present invention;

[0024] Figure 2 is an enlarged view of point A provided in an embodiment of the present invention;

[0025] Figure 3 is a schematic diagram of the development of an internally threaded copper tube provided by an embodiment of the present invention;

[0026] Figure 4 It is a schematic diagram of the actual surface and the bonding surface of the composite tube provided by the embodiment of the present invention;

[0027] Figure 5 Schematic diagram of cross section and longitudinal section of a composite tube provided by an embodiment of the present invention;

[0028] Figure 6 is a topographical diagram of the inner fin tooth shape provided by an embodiment of the present invention;

[0029] Figure 7 is a morphology diagram of a fin tube provided in an embodiment of the present invention;

[0030] Figure 8 is a schematic cross-sectional view of a titanium-aluminum composite pipe provided in an embodiment of the present invention;

[0031] Fig. 9 is a schematic diagram of the manufacturing principle of a heat exchange tube provided in an embodiment of the present invention;

[0032] Fig.10 is a schematic diagram of the front shape of a fin tube provided by an embodiment of the present invention;

[0033] Fig.11 It is a cross-sectional view of a fin tube provided in an embodiment of the present invention.

[0034] Reference numerals

[0035] 1-titanium tube outer wall, 2-smooth back teeth, 3-three-level step teeth, 4-nitrogen pipe, 5-feeder, 6-mother tube, 7-casting furnace, 8-composite layer, 9-mold and crystallizer, 10-traction machine, 11-channel tube, 12-stopper rod, 13-melting furnace. DETAILED DESCRIPTION

[0036] In order to make the technical personnel in the technical field better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in combination with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish different objects rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, device, product or end including a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or units inherent to these processes, methods, products or ends.

[0038] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0039] At present, the low efficiency of titanium tube heat exchangers has become an important factor restricting enterprise costs. If materials with higher heat transfer coefficients can be selected to replace traditional titanium tubes, their heat transfer efficiency can be greatly increased, thereby reducing energy consumption. However, traditional materials with relatively high heat transfer coefficients, such as copper and aluminum, are not suitable as heat exchange tubes for such working conditions due to their corrosion resistance. Therefore, it is necessary to produce a composite tubular composite material with high bonding strength to replace traditional titanium heat exchange tubes. The inner wall is made of titanium material for corrosion resistance, and the outer layer is an aluminum-copper composite material to increase heat exchange, achieve energy saving and consumption reduction, and reduce costs for enterprises.

[0040] The present invention aims to provide a tubular composite material with an internally threaded external fin structure and a preparation process thereof, so as to solve the problems of low temperature and pressure resistance of the composite pipe, easy deformation, damage and leakage after high-pressure washing, weak resistance to atmospheric corrosion, low heat exchange efficiency, high production cost and low production efficiency.

[0041] The specific embodiment of the present invention provides a tubular composite material with an internal thread and an external fin structure and a preparation process thereof, comprising the following steps:

[0042] S1: Use titanium tube and process internal threads inside the titanium tube.

[0043] In the embodiment of the present invention, the standards for the selected titanium tube are: the wall thickness of the titanium tube is 0.3mm-15mm, and the diameter is 5mm-80mm; the standards for the internal thread processing in the titanium tube are: the internal thread tooth height is 0.05mm-6mm; the tooth bottom wall thickness is 0.25mm-9mm; the tooth top angle is 25-75°; the number of internal threads is 35-500 per week; the tooth shape is a special-shaped tooth or a cross tooth; the surface area of ​​the titanium tube can be greatly increased by processing the internal thread, and the turbulence of the heat exchange medium in the tube can be increased. At the same time, the wall thickness of the titanium tube itself is certain. By processing the internal thread, the wall thickness of the titanium tube can be thinned to a certain extent, and the heat exchange conditions can be improved, thereby achieving the purpose of improving the heat exchange efficiency per unit length, which is matched with the heat exchange of the post-processing clad aluminum material.

[0044] S2: Copper-aluminum alloy is used as the surface cladding layer of the titanium tube, a small amount of titanium is added to the copper-aluminum alloy, and an electromagnetic stirrer is used to stir the alloy, and a refining agent is added during the stirring process for refining.

[0045] In an embodiment of the present invention, the contents of copper, aluminum and titanium elements in the surface cladding layer are: copper content is 50%-70%, aluminum content is 30%-50%, and titanium content is 0.5%-1.5%; the stirring speed of the electromagnetic stirrer is: 50r-300r / min, and the stirring time is 5-30min; the time for refining by adding the refining agent during the stirring process is: 10-20min.

[0046] S3: The copper-aluminum alloy liquid is melted, the titanium tube is pretreated, and the titanium tube is inserted, the titanium tube is emptied, and the liquid is discharged, and the cladding and traction are performed to prepare a composite alloy tube.

[0047] In an embodiment of the present invention, a copper-aluminum alloy is loaded into a melting furnace, and heated to 1300° C. by a heating coil and kept warm until all the aluminum is melted; at the same time, the holding furnace is turned on for heating, and the temperature is set to be 10° C. lower than the temperature of the melting furnace to obtain an alloy melt; the titanium tube is cleaned and degreased to remove surface dirt and an oxide layer; the titanium tube is inserted, the titanium tube is emptied, and the liquid is discharged, and the cladding traction is performed to prepare a composite alloy tube, including: the titanium tube insertion step is: opening the upper and lower traction rollers of the traction machine, inserting the titanium tube into the upper and lower traction rollers, until it passes through the upper traction roller, the center sleeve, the mold, and the lower traction roller, The upper and lower traction rollers are clamped, and a protective gas delivery pipe is inserted into the upper end of the titanium tube to continuously fill it with protective gas; the titanium tube idling step is: turn on the traction machine, and use the traction roller to drive the titanium tube to idling, and the speed is controlled at 20mm / min-100mm / min; the liquid discharge step is: open the stopper rod to allow the alloy melt to flow to the holding furnace through the liquid discharge channel; the cladding traction step is: after the alloy melt enters the holding furnace, the traction machine speed is adjusted to 100mm / min-1500mm / min, and cooling water is introduced for cooling, so that the alloy melt quickly crystallizes and is clad on the surface of the titanium tube to form a coating layer to obtain a composite alloy tube.

[0048] S4: During the preparation of the composite alloy tube, cladding and pulling are performed, and diffusion bonding heat treatment is performed after the cladding and pulling step.

[0049] In an embodiment of the present invention, the composite alloy tube is heated by raising the temperature of the heating furnace to 350°C-500°C and maintaining a heat preservation state, with a heat preservation pressure of 5MPa-15Mpa and a heat preservation time of 2h-5h, so that the atoms can fully diffuse; after the heat preservation state ends, the composite alloy tube is cooled by air cooling or water cooling.

[0050] S5: Processing the outer fins of the composite alloy tube to obtain an inner thread outer fin tubular composite material.

[0051] In an embodiment of the present invention, a fin rolling mill is used to adjust the rolling CNC blades and perform rolling on the machine to roll a circle of aluminum fins on the surface of the composite alloy tube to obtain an aluminum fin tube; the two ends of the aluminum fin tube are headed, and the fins are removed from the two ends of the aluminum fin tube to obtain an internally threaded externally finned tubular composite material; the aluminum fin wall thickness of the aluminum fin tube is 0.5mm-15mm, and the diameter is 5mm-80mm; the wall thickness of the composite alloy tube is 1mm-20mm, and the diameter is 5.5mm-90mm; the spacing between the composite alloy tube and the mold is 0.5-10mm; the distance between adjacent aluminum fins is 1.8mm-10mm, the sheet height is 0-20mm, and the sheet thickness is 0.2-1mm; after the outer fins of the composite alloy tube are processed to obtain an internally threaded externally finned tubular composite material, it also includes: removing oil stains and oxide layers on the surface of the internally threaded externally finned tubular composite material through the steps of degreasing-deoxidation film-cleaning-natural color passivation-cleaning and drying. 1. Material selection for the cladding layer:

[0052] The wall thickness of titanium tube is 0.3mm-15mm, and the diameter is 5mm-80mm;

[0053] Internal thread height is 0.05mm-6mm

[0054] Tooth bottom wall thickness 0.25mm-9mm Tooth top angle 25-75°

[0055] Internal thread quantity 35-500 / week

[0056] The tooth shape is special-shaped teeth or cross teeth, such as Figure 1-3 shown.

[0057] 2. Cladding material selection:

[0058] Example 1

[0059] 1. Material composition and preparation process

[0060] Raw material preparation: electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, and copper, aluminum and titanium are weighed in a mass ratio of 69:30:1.

[0061] Melting and casting: Add the weighed copper block into a graphite crucible and heat it to 1300℃ in a melting furnace to melt it completely. Then, slowly add the aluminum block and titanium material preheated to 550℃ into the copper liquid several times and stir evenly with an electromagnetic stirrer. The electromagnetic stirring speed is 200r / min and the stirring time is 15min to make the alloy composition uniform. Then, add refining agent into the melt for refining and impurity removal. The refining time is 10min. Then, use the ingot guide rod to pull out the ingot with a diameter of 30mm.

[0062] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0063] Example 2

[0064] 1. Material composition and preparation process

[0065] Raw material preparation: Electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials. The mass ratio is adjusted to 50:49:1.

[0066] Melting and casting: The melting process of copper is the same as that of Example 1. After the aluminum block and titanium material are added, the stirring speed is 180 r / min, the stirring time is 20 min, the refining time of the refining agent is 12 min, and then the ingot rod is used to pull out the ingot with a diameter of 30 mm.

[0067] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0068] Example 3

[0069] 1. Material composition and preparation process

[0070] Raw material preparation: Electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, with a mass ratio of 30:69:1.

[0071] Melting and casting: After the copper is melted, the stirring speed is 220r / min when the aluminum block is added, the stirring time is 18min, the refining agent is refined for 15min, and then the ingot rod is used to pull out the ingot with a diameter of 30mm.

[0072] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0073] 2. Comparison

[0074] Comparative Example 1 (pure copper material)

[0075] 1. Materials and processing: Electrolytic copper with a purity of 99.9% is directly used, heated to 1300 degrees Celsius to melt it, and then a dummy rod is used to pull out a casting billet with a diameter of 30 mm.

[0076] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0077] Comparative Example 2 (pure aluminum material)

[0078] 1. Materials and processing: Industrial pure aluminum with a purity of 99.9% is used, heated to 750 degrees Celsius to melt it, and then a dummy rod is used to pull out a casting billet with a diameter of 30 mm.

[0079] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0080] Comparative Example 3 (conventional copper, aluminum and titanium mixture without stirring)

[0081] Raw material preparation: electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, and copper, aluminum and titanium are weighed in a mass ratio of 69:30:1.

[0082] The weighed copper block is added into a graphite crucible and heated to 1300°C in a smelting furnace to completely melt it. Then, the aluminum block and titanium material preheated to 550°C are slowly added into the copper liquid several times. Refining agent is added into the melt for refining and impurity removal. The refining time is 10 minutes. After that, a dummy rod is used to pull out a cast billet with a diameter of 30 mm.

[0083] Comparative Example 4 (conventional copper, aluminum and titanium mixture without refining)

[0084] Raw material preparation: electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, and copper, aluminum and titanium are weighed in a mass ratio of 69:30:1.

[0085] The weighed copper block is added into a graphite crucible and heated to 1300°C in a smelting furnace to completely melt it. Then, an aluminum block preheated to 550°C is slowly added into the copper liquid several times and stirred evenly with an electromagnetic stirrer at a speed of 200r / min and a stirring time of 15min to make the alloy composition uniform. After that, a dummy rod is used to pull out a cast billet with a diameter of 30mm.

[0086] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0087] Comparative Example 5 (Increasing the proportion of TA1 to 5%)

[0088] 1. Material composition and preparation process

[0089] Raw material preparation: electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, and copper, aluminum and titanium are weighed in a mass ratio of 65:30:5.

[0090] Melting and casting: add the weighed copper block into the graphite crucible, heat it to 1300℃ in the melting furnace to make it completely melted, then slowly add the aluminum block and titanium material preheated to 550℃ into the copper liquid several times, and stir evenly with an electromagnetic stirrer at a speed of 200r / min and a stirring time of 15min to make the alloy composition uniform; then add a refining agent into the melt for refining and impurity removal, and the refining time is 10min. Then use the dummy rod to pull out the ingot with a diameter of 30mm.

[0091] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0092] Comparative Example 6 (Copper and aluminum mixed without adding titanium to refine grains)

[0093] 1. Material composition and preparation process

[0094] Raw material preparation: Electrolytic copper with a purity of 99.7% and industrial pure aluminum with a purity of 99.5% are selected as raw materials. Copper and aluminum are weighed in a mass ratio of 70:30:

[0095] Melting and casting: add the weighed copper block into the graphite crucible, heat it to 1300℃ in the melting furnace to make it completely melted, then slowly add the aluminum block preheated to 550℃ into the copper liquid several times, and stir it evenly with an electromagnetic stirrer at a speed of 200r / min and a stirring time of 15min to make the alloy composition uniform; then add a refining agent into the melt for refining and impurity removal, and the refining time is 10min. Then use the dummy rod to pull out the ingot with a diameter of 30mm.

[0096] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0097] Comparative Example 7 (Change in Ratio between Copper, Aluminum and Titanium)

[0098] 1. Material composition and preparation process

[0099] Raw material preparation: electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, and copper, aluminum and titanium are weighed in a mass ratio of 1:1:1.

[0100] Melting and casting: Add the weighed copper block into a graphite crucible and heat it to 1300℃ in a melting furnace to melt it completely. Then slowly add the aluminum block and copper material preheated to 550℃ into the copper liquid several times and stir evenly with an electromagnetic stirrer. The electromagnetic stirring speed is 200r / min and the stirring time is 15min to make the alloy composition uniform. Then add refining agent into the melt for refining and impurity removal. The refining time is 10min. After that, use the ingot guide rod to pull out the ingot with a diameter of 30mm.

[0101] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0102] Comparative Example 8 (Change in Ratio between Copper, Aluminum and Titanium)

[0103] 1. Material composition and preparation process

[0104] Raw material preparation: electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, and copper, aluminum and titanium are weighed in a mass ratio of 80:15:5.

[0105] Melting and casting: add the weighed copper block into the graphite crucible, heat it to 1300℃ in the melting furnace to make it completely melted, then add the aluminum block and titanium material preheated to 550℃ into the copper liquid, and stir evenly with an electromagnetic stirrer at a speed of 200r / min for 15min to make the alloy composition uniform, then add a refining agent into the melt for refining and impurity removal, and the refining time is 10min. Then use the dummy rod to pull out the ingot with a diameter of 30mm.

[0106] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0107] Comparative Example 9 (Change in Ratio between Copper, Aluminum and Titanium)

[0108] 1. Material composition and preparation process

[0109] Raw material preparation: electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5% and TA1 titanium material are selected as raw materials, and copper, aluminum and titanium are weighed in a mass ratio of 22.5:77:0.5.

[0110] Melting and casting: add the weighed copper block into the graphite crucible, heat it to 1300℃ in the melting furnace to make it completely melted, then slowly add the aluminum block and titanium material preheated to 550℃ into the copper liquid several times, and stir it evenly with an electromagnetic stirrer at a speed of 200r / min and a stirring time of 15min to make the alloy composition uniform; then add a refining agent into the melt for refining and impurity removal, and the refining time is 10min. Then use the dummy rod to pull out the ingot with a diameter of 30mm.

[0111] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0112] Comparative Example 10 (Change in the ratio between copper, aluminum and titanium)

[0113] 1. Material composition and preparation process

[0114] Raw material preparation: Electrolytic copper with a purity of 99.7%, industrial pure aluminum with a purity of 99.5%, and TA1 titanium material are selected as raw materials. Copper, aluminum, and titanium are weighed in a mass ratio of 20:20:60.

[0115] Melting and casting: Add the weighed titanium material into a graphite crucible, heat it to 1700℃ in a melting furnace to completely melt it, then slowly add aluminum blocks and copper blocks preheated to 550℃ into the copper liquid several times, and stir evenly with an electromagnetic stirrer at a speed of 200r / min for 15min to make the alloy composition uniform. Then add a refining agent to the melt for refining and impurity removal, and the refining time is 10min. Then use a dummy rod to pull out a 30mm diameter ingot.

[0116] Rolling forming: The ingot was cast and extruded by a rolling mill at a rolling speed of 5 mm / s to obtain a rod with a diameter of 20 mm.

[0117] Experimental results:

[0118]

[0119] Note: Test method:

[0120] Thermal conductivity test: The thermal conductivity of the material is measured by laser flash method, and the test temperature is 25℃.

[0121] Cold bending performance test: cold bending test is carried out in accordance with the national standard GB / T 232-2010 "Metallic Material Bending Test Method". The bar is processed into a specimen with a width of 20mm and a thickness of 5mm, the diameter of the bending pressure head is 10mm, and the bending angle is 180°.

[0122] Elongation at break test: Use a tensile testing machine to test the elongation at break, the sample gauge length is 50 mm, and the stretching speed is 2 mm / min; the formula is (Lend-Linitial) / Linitial*100%, where Lend is the gauge length after breaking, and Linitial is the original gauge length.

[0123] Insert titanium tube wall thickness measurement: insert a titanium tube with a wall thickness of 0.4 mm into the high-temperature molten metal liquid in the examples and comparative examples, and quickly take out the titanium tube after 10 seconds to remove the residual slag liquid on the surface, and measure the residual wall thickness of the titanium tube.

[0124] It can be seen from the above embodiments and comparative examples that different copper-aluminum contents and different preparation processes have significant effects on the thermal conductivity and cold bending properties of the copper-aluminum composite material. ; Within a certain range, as the copper content increases, the thermal conductivity increases, but the cold bending performance will change; the added TA content can significantly improve the plasticity of the material within a suitable ratio range, and the effect on its thermal conductivity can be ignored, but when the proportion of titanium added is too high, its thermal conductivity will be significantly reduced; and the optimized preparation process (refining and slag removal and electromagnetic homogenization stirring) can significantly improve the comprehensive performance of the material, making it perform better in thermal conductivity and cold bending. If electromagnetic stirring is not performed, the aluminum liquid and the copper liquid will be unevenly mixed, resulting in uneven composition of the ingot structure, resulting in formation differences at different positions, and severe cracking in some areas of comparative example 3; unrefined impurities will not be effectively removed, resulting in ingot inclusions, and there is a possibility of defects in the performance of the inclusion area, resulting in point cracks in comparative example 4; therefore, the copper-aluminum composite material is applied to the cladding layer, and its performance has better application potential than pure copper, pure aluminum and materials prepared by unoptimized processes.

[0125] 3. Preparation of composite pipe materials:

[0126] The titanium tube is inserted into the mold with a certain distance between the tube (core layer) and the mold. The skin alloy liquid is drained to the gap between the tube (core layer) and the mold, and cooled by water outside the mold. The skin alloy liquid is cooled outside the tube (core layer) and seamlessly attached to the tube (core layer) to obtain a composite alloy tube with suitable wall thickness and outer diameter.

[0127] The specific process is:

[0128] Titanium tube pretreatment - inserting titanium tube - emptying titanium tube - draining liquid - cladding traction

[0129] Melting of copper-aluminum alloy liquid: Place an appropriate amount of copper-aluminum alloy materials in the melting furnace, use the heating coil to heat to 1300℃ and keep warm until the aluminum is completely melted, and turn on the insulation furnace to heat, and the temperature is set to be 10 degrees lower than the melting furnace temperature.

[0130] Titanium tube pretreatment: Clean and degrease the titanium tube to remove dirt and oxide layer on the surface to ensure the quality and bonding strength of the aluminum coating.

[0131] Insert the titanium tube: open the upper and lower traction rollers, insert the titanium tube until it passes through the upper traction roller, the center sleeve, the mold, and the lower traction roller. Clamp the upper and lower traction rollers, and then insert the protective gas delivery pipe into the upper end of the titanium tube. Continuously fill it with protective gas. The protective gas should not react with titanium and aluminum at high temperatures, and can effectively prevent the tube wall from reacting with oxygen, nitrogen and other gases at high temperatures to cause changes in material structure.

[0132] Titanium tube empty running: Turn on the traction machine and use the traction roller to drive the titanium tube to empty running. The speed is controlled at 20mm / min-100mm / min. The purpose is to prevent the subsequent alloy liquid from quickly crystallizing and getting stuck after entering the holding furnace.

[0133] Tapping: Open the stopper rod to allow the molten alloy to flow into the holding furnace through the tapping channel.

[0134] Cladding traction: After the alloy melt enters the holding furnace, the traction machine speed is adjusted to 100-1500mm / min. Through the cooling of cooling water, the alloy melt is quickly crystallized and clad on the surface of the titanium tube to form a coating layer and a composite alloy tube.

[0135] The nitrogen protection device is a metal air pipe filled with dry protective gas. During the production of the blank tube, dry protective gas is continuously filled to protect the inner wall from oxidation and high-temperature reaction, avoiding oxidation and decarburization of the inner wall.

[0136] An alloy composite tube, characterized in that the wall thickness of the composite tube is 1mm-20mm, the diameter is 5.5mm-90mm, such as Figure 4 , Figure 5 As shown, the surface of the alloy composite pipe is smooth, the cladding is full, and the bonding surface is metallurgical bonding, which is not a "two-layer skin".

[0137] 4. Diffusion combined heat treatment of composite tube:

[0138] At a temperature above half of the melting point of aluminum, pressure is applied to keep the atoms on the bonding surface within the bonding distance, and appropriate pressure is provided to allow them to plastically flow to the abnormal void area that needs to be filled, so that they can achieve a seamless and vacuum-free state while achieving a metallurgical bonding as a whole, further enhancing their bonding strength.

[0139] A heating temperature of an alloy tube: characterized in that the heating temperature is 350°C-500°C.

[0140] A kind of alloy pipe insulation pressure: characterized by the pressure of 5MPa-15Mpa.

[0141] A heat preservation time of an alloy tube: characterized by 2H-5H.

[0142] One method of cooling the alloy tube is air cooling or water cooling.

[0143] 5. Processing of outer fins:

[0144] Through the fin rolling mill, the rolling CNC blade is adjusted, and the machine is rolled to roll a circle of aluminum fins on the aluminum cladding surface of the composite material. The processing depth (thickness) and fin density (pitch) of the fins can be adjusted according to the thickness of the aluminum cladding and the use requirements. After the fin tube is completed, the ends of the fin tube are dialed, and the fins are removed at both ends of the fin tube according to the required length to facilitate the later installation on the heat sink. It is installed on the end plate structure of the fin tube radiator, and the overlapping staggered arrangement is adopted to maintain turbulence and enhance the gas heat dissipation performance.

[0145] A composite continuous casting fin tube, such as Figure 6-11 As shown, it is characterized in that the wall thickness of the tube (core layer) is 0.5mm-15mm, and the diameter is 5mm-80mm; the wall thickness of the composite tube is 1mm-20mm, and the diameter is 5.5mm-90mm.

[0146] A fin manufacturing method, characterized in that the distance between the alloy tube (core layer) and the mold is 0.5-10mm.

[0147] The fin tube sheet distance is 1.8mm-10mm, the sheet height is 0-20mm, and the sheet thickness is 0.2-1mm.

[0148] 6. Fin tube post-processing:

[0149] The oil stains and oxidation layer on the surface of the internally threaded external fin tubular composite material are removed in the order of degreasing, removing oxidation film, cleaning, natural color passivation, cleaning and drying.

[0150] Embodiment 1:

[0151] The titanium tube has a wall thickness of 0.8mm, a tube diameter of 19.5mm, a processing internal thread tooth height of 0.3mm, a tooth bottom wall thickness of 0.5mm, a tooth top angle of 35°, a cross-tooth form, 220 internal threads, a casting temperature of 680°C, a traction speed of 200mm / min, a cladding layer thickness of 1mm, and a composite tube diameter of 21.5mm; the fin tube sheet spacing is 2mm, the sheet height is 0.55mm, the sheet thickness is 0.3mm, and the diffusion bonding heat treatment is 450°C. The insulation pressure is 10MPa and the insulation time is 3H.

[0152] Embodiment 2:

[0153] The wall thickness of the titanium tube is 0.5mm, the diameter of the tube is 19mm, the processing internal thread tooth height is 0.2mm, the tooth bottom wall thickness is 0.3mm, the tooth top angle is 40°, the form of heterosexual teeth is adopted, the number of internal threads is 180, the casting temperature is 880℃, the pulling speed is 400mm / min, the cladding layer thickness is 1.5mm, and the composite tube diameter is 22mm; the fin tube segment distance is 4mm, the segment height is 1.3mm, the segment thickness is 0.8mm, and the diffusion bonding heat treatment is 400℃; the insulation pressure is 12MPa, and the insulation time is 4H.

[0154] Comparative Example 1:

[0155] The wall thickness of the titanium tube is 0.8mm, the diameter of the tube is 19.5mm, the processing internal thread tooth height is 0.3mm, the tooth bottom wall thickness is 0.5mm, the tooth top angle is 35°, the cross tooth form is adopted, the number of internal threads is 220, the casting temperature is 1200℃, the pulling speed is 200mm / min, the cladding layer thickness is 1mm, and the composite tube diameter is 21.5mm; the fin tube pitch is 2mm, the sheet height is 0.55mm, the sheet thickness is 0.3mm, and the diffusion bonding heat treatment is 450℃; the insulation pressure is 10MPa, and the insulation time is 3H.

[0156] Comparative Example 2:

[0157] The wall thickness of the titanium tube is 0.5mm, the diameter of the tube is 19mm, the processing internal thread tooth height is 0.2mm, the tooth bottom wall thickness is 0.3mm, the tooth top angle is 40°, the form of heterosexual teeth is adopted, the number of internal threads is 180, the casting temperature is 880℃, the pulling speed is 20mm / min, the cladding layer thickness is 1.5mm, and the composite tube diameter is 22mm; the fin tube pitch is 4mm, the sheet height is 1.3mm, the sheet thickness is 0.8mm, and the diffusion bonding heat treatment is 400℃; the insulation pressure is 12MPa, and the insulation time is 4H.

[0158] Comparative Example 3:

[0159] The wall thickness of the titanium tube is 0.5mm, the diameter of the tube is 19mm, the processing internal thread tooth height is 0.2mm, the tooth bottom wall thickness is 0.3mm, the tooth top angle is 40°, the form of heterosexual teeth is adopted, the number of internal threads is 180, the casting temperature is 880℃, the pulling speed is 2000mm / min, the cladding layer thickness is 1.5mm, and the composite tube diameter is 22mm; the fin tube pitch is 4mm, the sheet height is 1.3mm, the sheet thickness is 0.8mm, and the diffusion bonding heat treatment is 400℃; the insulation pressure is 12MPa, and the insulation time is 4H.

[0160]

[0161] The beneficial effects of the present invention are embodied in that the composite pipe produced by the production process has high overall temperature and pressure resistance, will not be deformed, damaged or leaked after high-pressure washing, has strong atmospheric corrosion resistance and high heat exchange efficiency. The overall weight of the pipe is light and can achieve overall lightweight. At the same time, due to the overall use of the composite continuous casting production process, the overall production cost is low, the production efficiency is high, and long-size continuous production can be achieved. It can be produced over a long distance according to demand, without welding, without welds, and can effectively respond to special production needs. And through the directional combination of mold design and internal base pipe, composite pipes with different processes and different wall thicknesses are produced, thereby realizing diversified and customized production; wherein, the inner titanium tube has high strength and pressure bearing capacity, can maintain the overall rigidity of the element, is not prone to deflection and deformation, can be used for a long time, and plays a supporting structure role in the later overall structural combination of the heat exchanger, has strong pressure resistance, and can work stably in various harsh environments. In addition, the biggest advantage of the titanium tube is overall corrosion resistance, so it can flow through highly corrosive acid, alkali, and salt chemical solutions. The outer aluminum-copper cladding has excellent thermal conductivity, which can greatly improve the overall heat transfer efficiency of the component.

[0162] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical schemes or characteristics in the scheme is not described in detail here; it should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the scheme of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the present invention and the practicality of the patent. The protection scope required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A tubular composite material with an internal thread and an external fin structure and a preparation process thereof, characterized in that: The method comprises: S1: Select a titanium tube and perform internal thread processing in the titanium tube; S2: using a copper-aluminum alloy as the surface cladding layer of the titanium tube, adding a small amount of titanium to the copper-aluminum alloy, stirring the alloy by an electromagnetic stirrer, and adding a refining agent during the stirring process for refining; S3: melting the copper-aluminum alloy liquid, pre-treating the titanium tube, inserting the titanium tube, idling the titanium tube, draining the liquid, and performing cladding traction to prepare a composite alloy tube; S4: During the preparation process of the composite alloy tube, cladding traction is performed, and diffusion bonding heat treatment is performed after the cladding traction step; S5: Processing the outer fins of the composite alloy tube to obtain an internally threaded outer fin tubular composite material.

2. The tubular composite material with an internal thread and external fin structure and its preparation process according to claim 1, characterized in that: The standard of the titanium tube selected is: the wall thickness of the titanium tube is 0.3mm-15mm, and the diameter is 5mm-80mm; The standards for the internal thread processing in the titanium tube are: internal thread tooth height is 0.05mm-6mm; tooth bottom wall thickness is 0.25mm-9mm; tooth top angle is 25-75°; the number of internal threads is 35-500 per week; and the tooth shape is special-shaped teeth or cross teeth.

3. The tubular composite material with an internal thread and external fin structure and its preparation process according to claim 2, characterized in that: The contents of copper, aluminum and titanium in the surface cladding layer are as follows: the copper content is 50%-70%, the aluminum content is 30%-50%, and the titanium content is 0.5%-1.5%.

4. The tubular composite material with an internal thread and external fin structure and its preparation process according to claim 3, characterized in that: The stirring speed of the electromagnetic stirrer is 50r-300r / min, and the stirring time is 5-30min; The time for refining by adding the refining agent during the stirring process is 10-20 minutes.

5. The tubular composite material with an internal thread and external fin structure and its preparation process according to claim 4, characterized in that: The step of pre-treating the titanium tube by melting the copper-aluminum alloy liquid comprises: The copper-aluminum alloy is placed in a melting furnace, and heated to 1300° C. by a heating coil and kept warm until all the aluminum is melted; At the same time, the holding furnace is turned on for heating, and the temperature is set to be 10° C. lower than the temperature of the melting furnace to obtain alloy melt; The titanium tube is cleaned and degreased to remove dirt and oxide layer on the surface.

6. The tubular composite material with an internal thread and external fin structure and its preparation process according to claim 5, characterized in that: The steps of inserting the titanium tube, idling the titanium tube, draining the liquid, and performing cladding traction to prepare the composite alloy tube include: The titanium tube inserting step is: opening the upper and lower traction rollers of the traction machine, inserting the titanium tube into the upper and lower traction rollers until it passes through the upper traction roller, the center sleeve, the mold, and the lower traction roller, clamping the upper and lower traction rollers, inserting a protective gas delivery pipe into the upper end of the titanium tube, and continuously filling it with protective gas; The titanium tube idling step is: turning on the traction machine, using the traction roller to drive the titanium tube idling, and controlling the speed at 20mm / min-100mm / min; The tapping step comprises: opening the stopper rod to allow the alloy melt to flow to the holding furnace through the tapping channel; The cladding and traction step is as follows: after the alloy melt enters the holding furnace, the traction machine speed is adjusted to 100mm / min-1500mm / min, and cooling water is introduced to cool the alloy melt so that the alloy melt quickly crystallizes and clads on the surface of the titanium tube to form a coating layer to obtain a composite alloy tube.

7. The tubular composite material with an internal thread and external fin structure and its preparation process according to claim 6, characterized in that: In the process of preparing the composite alloy tube, cladding traction is performed, and after the cladding traction step, a diffusion combined heat treatment step is performed, comprising: The composite alloy tube is heated by increasing the temperature of the heating furnace to 350° C.-500° C. and maintaining the heat preservation state, wherein the heat preservation pressure is 5 MPa-15 MPa and the heat preservation time is 2 h-5 h, so that the atoms can be fully diffused; After the heat preservation state ends, the composite alloy tube is cooled by air cooling or water cooling.

8. The tubular composite material with an internal thread and external fin structure and its preparation process according to claim 1, characterized in that: The step of processing the outer fin of the composite alloy tube to obtain an internally threaded externally finned tubular composite material comprises: By using a fin rolling mill, adjusting a rolling numerical control blade, and rolling on the machine, a circle of aluminum fins is rolled on the surface of the composite alloy tube to obtain an aluminum fin tube; The two ends of the aluminum fin tube are headed, and the fins are removed from the two ends of the aluminum fin tube to obtain an internally threaded externally finned tubular composite material.

9. The tubular composite material with an internal thread and external fin structure and the preparation process thereof according to claim 8, characterized in that: The aluminum fin tube has an aluminum fin wall thickness of 0.5mm-15mm and a diameter of 5mm-80mm; The composite alloy tube has a wall thickness of 1 mm to 20 mm and a diameter of 5.5 mm to 90 mm; The distance between the composite alloy tube and the die is 0.5-10 mm; The distance between adjacent aluminum fins is 1.8mm-10mm, the height is 0-20mm, and the thickness is 0.2-1mm.

10. The tubular composite material with an internal thread and external fin structure and the preparation process thereof according to claim 9, characterized in that: After the outer fins of the composite alloy tube are processed to obtain the internally threaded externally finned tubular composite material, the method further includes: removing oil stains and oxidation layers on the surface of the internally threaded externally finned tubular composite material by the steps of degreasing - removing oxidation film - cleaning - natural color passivation - cleaning and drying.

Citation Information

Cited By

  • Composite pipe production method

    CN121820395A